Leopard and its mythological-epic motifs in Shahnameh and four other epic works (Garshasbnameh, Kushnameh, Bahmannameh and Borzunameh) - Sharifizad, Nasrin (2021)
In Shahnameh and other epic poems where the reflection of myths is the life of primitive and ancient Iranian communities, animals and other creatures are of great importance and go beyond their normal features and position. Myths that are the facts from the thoughts and ideas of the early man are mixed with different stories and are expressed symbolically and mysteriously.  Among the animals, “leopard” is one of the role players whose name has been mentioned in Ferdowsi’s Shahnameh and other epic poems and has accounted for themes and motifs. This paper seeks to examine the place of leopard in past myths and civilization as well as in the most valuable epic work, i.e. Shahnameh, and four other epic poems (Garshasbnameh, Kushnameh, Bahmannameh and Borzunameh) and extract, classify and analyze the most important mythological-epic and ritual motifs of this animal. These motifs include the lexical and symbolic meaning of leopard, the position of leopard in the myths and civilization of ancient Iran, the relationship between the goddesses and the leopard, the characteristics of leopard, child and leopard, leopard skin as a garment, metamorphosis, leopard in the welcome ceremony, leopard skin as a gift, demonic creature, leopard totem, leopard as war booty, leopard in the treasure of kings and leopard spell. The concept or symbol of the leopard in this research relies on its positive aspect, sometimes it is one of the goddesses and is respected and sometimes it is a symbol of courage, strength and victory.